The Influence of Graduate Attraction, Quality of Academic Services and School Image on the Decision To Become a New Student - Dias Lestari; Qristin Violinda; Heri Prabowo (Journal of Islamic Entrepreneurship and Business Research, 2024)
This study aims to examine the influence of graduate attraction, academic service quality, and school image on the decision to enroll as a new student at SMK HKTI Temanggung. This research utilizes a quantitative approach, with primary data collected from the students of SMK HKTI Temanggung. The sample consists of 74 respondents, selected using the Probability Sampling technique. A Likert scale was used to measure the variables, and the data was analyzed using IBM SPSS Statistics Version 25 through multiple linear regression analysis. The results of the coefficient of determination (R2) test indicate that the Adjusted R Square value is 0.375, or 37.5%. This suggests that the decision to enroll as a new student is influenced by the variables of graduate attraction, academic service quality, and school image. The remaining 62.5% of the decision is influenced by other factors not included in this study. The findings highlight the importance of graduate attraction, the quality of academic services, and the image of the school in shaping prospective students' decisions to enroll. The results of this study offer valuable insights for the management of SMK HKTI Temanggung, emphasizing the need to enhance the factors that influence students' decisions, such as improving the quality of academic services and promoting a positive school image. These findings can guide the school in formulating strategies to attract more prospective students and improve its overall competitiveness in the education sector.